Relación entre la recaudación de ingresos y la ejecución de gastos en la Municipalidad Provincial de Loreto Nauta, 2016-2023 - Lopez Catashunga, Erick Alexander (2025)
The Provincial Municipality of Loreto-Nauta presented a financial performance characterized by marked fluctuations in its income and expenses. Total accumulated income was S/ 338,829,245, a 46.36% increase, while expenses reached S/ 360,803,277, growing by 40.60%. However, the increases were not proportional year over year. In 2019, income grew 280.12%, while expenses only increased 3.45%. In 2020, expenses soared 284.73% due to the pandemic. Statistical analysis using the Shapiro-Wilk normality test showed that income follows a normal distribution (p = 0.106), but expenses do not (p = 0.011), indicating greater volatility in the execution of public spending. Furthermore, Spearman's correlation coefficient yielded a value of 0.2619, with a p-value of 0.5309, indicating no statistically significant correlation between revenue and expenditure. These results show that there is no direct correlation between what is collected and what is spent, reflecting weaknesses in financial and budgetary planning. Spending has been unstable, and in some years, it has been executed without taking into account revenue trends. This affects the efficiency of public spending and the ability to address local needs.